Sailors’ Valentines: Shell Mosaics from Victorian Barbados - Molly Duggins (British Art Studies, 2023)
Octagonal shell mosaics---colloquially known as sailors' valentines---were produced in a cottage industry by black and brown Barbadian women for the burgeoning Caribbean tourism industry in the Victorian era. As a commercial colonial craft, sailors' valentines have been occluded in art historical discourse. Nevertheless, these vibrant collages foreground the multivalent significance of creolised material culture circulating within modernising colonial economies. Through their artful assemblage of shells, they not only embody the legacy of eighteenth-century natural philosophy and the picturesque movement, but also reflect diasporic West African spiritual and aesthetic practices engaged in creating an Afro-Barbadian cultural autonomy within a plantation society. This article traces the material evolution of sailors' valentines from their origins in British conchology and craft to their implication in the rise of international seaside leisure. Honing in on the adaptation of shell mosaics in the Victorian Caribbean as object emissaries of a post-emancipation island tourism economy, it considers how they were engaged in rebranding the British West Indies as a consumable natural wonderland. The article concludes with an assessment of contemporary sailors' valentines that invoke the creolisation of Barbadian shell mosaics to negotiate global cultural interchange, while critiquing the environmental legacy of the Victorian consumption of nature.